Non-aqueous titration of alkaloids and alkaloidal salts - Valmonte, Maria Lourdes (Arreola) 1924-
PURPOSE: 1) To titrate some official alkaloids and alkaloidal salts that are locally available using the perchloric-glacial acetic acid method, and to compare the results with those obtained by following official assay procedures, 2)to determine the feasibility of employing this non-aqueous method as a substitute for official assay procedures, or as a method of assay for those official alkaloids that do not have assay methods included in their monographs. PROCEDURE: The dried alkaloidal sample was weighed, dissolved in anhydrous acetic acid, and titrated with standard perchloric acid in anhydrous acetic acid. Three indicators were used in these determinations: methyl violet, alpha-naphtholbenzein, and quinaldine red. Mercuric acetate solution was added to the solvent when titrating alkaloidal halides, and measured amounts of carbon tetrachloride when titrating purine alkaloids. The results were compared with those obtained by following official assay procedures. Approximate amount of time devoted to the investigation was about 15 months. DEGREE OF SUPERVISION: When difficulties in titration and extraction procedures were encountered, the problems were properly appraised, and solutions were suggested. The investigation contributed 25 analyzed alkaloids and alkaloidal salts, possibly the greatest number to be determined in any one single system. All materials, with a very few exceptions, were successfully titrated. The results of this investigation will be made part of a report to the Expert Committee on the International Pharmacopoeia on non-aqueous titration of pharmacopoeial substances.